Tingkat Kemampuan Literasi Media Baru Mahasiswa Universitas Riau - Muhamad Nurur Rijal; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The development of new media causing media content more and more, so that the control or sensor over media increasingly hard to do. Therefore, communities need alternative in order to be protected from the negative effects of new media. The concept for the challenges of the new media is a new media literacy concepts. Based on the foregoing, a new media literacy skills is essential to prepare and protect society from the negative impacts of new media. In addition, new media literacy is also important for improving the quality of new media. The purpose of this study was to determine the extent to which of new media literacy proficiency level of students at the University of Riau.The methods used in this research is quantitative descriptive survey method, the researchers collecting data using questionnaires. This research was conducted at the University of Riau with the total sample of 291 respondents research, and the collection using quota sampling technique. To determine the level of new media literacy skills of students at the University of Riau, researchers used a frequency distribution table makes it easy to authors to calculating the score of new media literacy skills level of students at the University of Riau.The results of this study showed that of the total 291 respondents new media literacy proficiency level the students of the University of Riau to use skill proficiency criteria more dominant on the basic level is 205 (70.45%) of the respondents, it means the ability of students at the University of Riau in the use of new media is not too high. Meanwhile, for new media skill level the critical understanding criteria more than dominant the skill medium level is 145 (49.83%) of the respondents, , it means the ability of students at the University of Riau in analyzing and evaluating new media content high enough. Next, the new media literacy skill level criterion of communicative abilities are more dominant in the skill level medium is 171 (58.77%) of the respondents, it means the ability of students at the University of Riau in the activity of producing new media content and social participation in new media content is high enough.Keywords: Ability Level, Literacy Media, New Media, Students of Riau University